FACTORS RELATED TO PATIENT SATISFACTION IN THE INHERATION OF GRANDED LUBUK PAKAM HOSPITAL - Layari Tarigan; Harris Rambey; Riska Litawati (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
A service is considered satisfactory if the service can meet the needs and expectations of customers. If reality is greater than expectations, the consumer is very satisfied. The advantages of health services provided include aspects of tangible, assurance, reliability, empathy, and responsiveness. Meanwhile, satisfaction is the response or level (pleasure or disappointment) of the patient obtained after the patient has received a health service product by comparing the perceived performance or outcome with the patient's needs and expectations. This type of research is a quantitative research that is an analytic survey with a cross sectional design which aims to determine the factors that are related to the quality of health services on the satisfaction of inpatients at Grandmed Lubuk Pakam which were observed at the same time. The population in this study were all 34 inpatients at Grandmed Lubuk Pakam based on an initial survey in 2022 at Grandmed Lubuk Pakam Hospital. The sample in this study were 34 inpatients at Grandmed Lubuk Pakam who were taken using a total sampling technique. The results of this study indicate that there is no relationship between the quality of health services in tangible dimensions (0.084> 05), empathy (0.088> 0.05), and responsiveness (0.058> 0.05), while reliability (0.05> 0.05). assurance (0,058>0,050). With patient satisfaction. The conclusion in this study is that there is no relationship with the quality of health services on inpatient satisfaction at Grandmed Lubuk Pakam.